2015
DOI: 10.1007/s13204-015-0422-x
|View full text |Cite
|
Sign up to set email alerts
|

Characterization and in vitro studies on anticancer, antioxidant activity against colon cancer cell line of gold nanoparticles capped with Cassia tora SM leaf extract

Abstract: This study was aimed to determine the effectiveness of synthesized gold nanoparticles of an ethnobotanically and medicinally important plant species Cassia tora against colon cancer cells and to find its antibacterial and antioxidant activities. In order to improve the bioavailability of C. tora, we synthesized gold nanoparticles through green synthesis, by simple mixing and stirring of C. tora leaf powder and tetrachloroauric acid (HAuCl 4 ) solution which gave a dispersion of gold nanoparticles conjugate wit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
12
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
5
3
2

Relationship

0
10

Authors

Journals

citations
Cited by 53 publications
(12 citation statements)
references
References 29 publications
(26 reference statements)
0
12
0
Order By: Relevance
“…It has been demonstrated before that AuNPs exert in vitro cytotoxicity on several human cancer cells including HepG2 and triple negative breast cancer cells (MDA-MB-231) [ 61 , 62 , 63 ]. Green-synthesized AuNPs from Cassia tora leaf extracts demonstrated the cytotoxic efficacy against colon cancer (Col320) cell lines and not in the normal (Vero) cell lines [ 64 ]. AuNPs from Gymnema sylvestre leaf extracts were also investigated for their antitumor effects against HT-29 cells.…”
Section: Resultsmentioning
confidence: 99%
“…It has been demonstrated before that AuNPs exert in vitro cytotoxicity on several human cancer cells including HepG2 and triple negative breast cancer cells (MDA-MB-231) [ 61 , 62 , 63 ]. Green-synthesized AuNPs from Cassia tora leaf extracts demonstrated the cytotoxic efficacy against colon cancer (Col320) cell lines and not in the normal (Vero) cell lines [ 64 ]. AuNPs from Gymnema sylvestre leaf extracts were also investigated for their antitumor effects against HT-29 cells.…”
Section: Resultsmentioning
confidence: 99%
“…In another study AuNPs targeted to the nucleus, promote cell-cycle arrest, cytokinesis inhibitionwhich then push the cell over to apoptosis [94]. In many instances, AuNPs are used as a delivery system [95] or in conjugation with the therapeutic molecule [96] or maybe even gene to give significantly better toxicity against cancer cells. AuNPs due to their distinctive photo-optical properties have been successfully applied in both photothermal and photodynamic therapy.…”
Section: Gold Nanoparticlesmentioning
confidence: 99%
“…Another study demonstrated the cytotoxic efficacy of Cassia tora against colon cancer cell lines. The study revealed that the activity of C. tora at three different doses (25, 50, and 75 μ g/mL) was dose-dependent; the 75 μ g/mL dose showed the highest activity against the colon cancer cell lines [ 108 ]. Green-synthesized AuNPs from Gymnema sylvestre leaf extracts ( G. sylvestre ) were also investigated for their anticancer effects against hepatocellular carcinoma (HepG2) cells.…”
Section: Aunpsmentioning
confidence: 99%